2021
DOI: 10.3389/fphys.2020.00718
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Bactericidal/Permeability-Increasing Protein Improves Cognitive Impairment in Diabetic Mice via Blockade of the LPS-LBP-TLR4 Signaling Pathway

Abstract: Emerging evidence suggests that the bactericidal/permeability-increasing protein (BPI) is involved in the process of cognitive impairment in diabetes. However, its underlying mechanism remains elusive. In this study, we found that BPI affects cognitive impairment due to diabetes through the lipopolysaccharide (LPS)-lipopolysacharide-binding protein (LBP)-toll-like receptor 4 (TLR4) signaling pathway. We examined the expression of BPI, LPS, LBP, CD14, and TLR4 in established mouse models of diabetes induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Furthermore, the negative correlation between object recognition memory performance and plasma IL-6 level has been observed. Our results were consistent with the previous research reporting increased levels of circulating TNF-α, IL-1β, and IL-6 in STZ-induced diabetic mice (Niu et al, 2016;Sun et al, 2021;Zhang et al, 2016). Interestingly, we found that the treatment with metformin reduced systemic pro-inflammatory cytokines levels in diabetic mice.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the negative correlation between object recognition memory performance and plasma IL-6 level has been observed. Our results were consistent with the previous research reporting increased levels of circulating TNF-α, IL-1β, and IL-6 in STZ-induced diabetic mice (Niu et al, 2016;Sun et al, 2021;Zhang et al, 2016). Interestingly, we found that the treatment with metformin reduced systemic pro-inflammatory cytokines levels in diabetic mice.…”
Section: Discussionsupporting
confidence: 93%
“…The bactericidal permeability-increasing protein (BPI) is an endogenous protein that in Type 2 Diabetes Mellitus can reduce inflammation [34]. In saliva, BPI was more abundant in patients with Type 2 Diabetes Mellitus than in healthy subjects (FC = 14.99), probably a reflection of the body's attempt to fight the inflammatory state characteristic of diabetes.…”
Section: Adaptative and Innate Immune Responsementioning
confidence: 99%